AIDS - Currie-McGhee, L. K. [ (Leanne K.)] (Detroit, MI : Lucent Books, 2008)
Describes AIDS, how it affects the world?s population, preventive programs, and various treatments available.
1. AIDS : past and present -- 2. The global impact -- 3. Women and children -- 4. The AIDS stigma -- 5. Fighting AIDS with prevention -- 6. Treating AIDS
Includes bibliographical references and index
Keywords: AIDS (Disease) -- Social aspects -- Juvenile literature; AIDS (Disease)